A study of heavy rainfall in and around Jaipur - GANESAN, GS; PRASAD, MC (MAUSAM, 1985)
Study of heavy rainfall in a city assumes great importance on account of its impact on various aspects of social life. Jaipur is situated in a semi-arid region of India. Study of heavy rainfall over Jaipur is, therefore, of added significance. The various aspects of heavy rainfall over Jaipur , by analysing the rainfall data of Jaipur and State raingauges in Rajasthan, extending over a period of 70 years (1901-70) are presented. Synoptic features responsible for the occurrence of these heavy spells are classified into various types.